Investigation of individual perceptions towards BIM implementation-a Chongqing case study. Issue 7 (18th June 2019) - Liu, Nan; Ruan, Lin; Jin, Ruoyu; Chen, Yunfeng; Deng, Xiaokang; Yang, Tong
Abstract : Purpose: The purpose of this paper is to target on individual perceptions of BIM practice in terms of BIM benefits, critical success factors (CSFs) and challenges in Chongqing which represented the less BIM-developed metropolitan cities in China. Design/methodology/approach: Adopting a questionnaire-survey approach followed by statistical analysis, the study further divided the survey population from Chongqing into subgroups according to their employer types and organization sizes. A further subgroup analysis adopting statistical approach was conducted to investigate the effects of employer type and organization size on individual perceptions. Findings: Subgroup analysis revealed that governmental employees held more conservative and neutral perceptions toward several items in BIM benefit, CSFs and challenges. It was inferred that smaller organizations with fewer than 100 full-time employees perceived more benefits of BIM in recruiting and retaining employees, and considered more critical of involving companies with BIM knowledge in their projects. Originality/value: This study contributed to the body of knowledge in managerial BIM in terms that: it extended the research of individual perceptions toward BIM implementation by focusing on less BIM-mature regions; it contributed to previous studies of influencing factors to BIM practice-based perceptions by introducing factors related to organization type and sizes; and it would lead to future research in establishing BIM climate and culture which address perceptions and behaviors in BIM adoption at both individual and organizational levels.